PENINGKATAN HASIL BELAJAR LEMPAR TURBO MELELUI PENDEKATAN MODIFIKASI PERMAINAN BOLA BEREKOR - Ilham, Ilham (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:Physical education provides an opportunity for all learners to be directly involved in various learning experiences through physical activity, play, and exercises that are done systematically, directed and programmed. But in reality always experience obstacles during the learning takes place. Less than maximal learning of turbo throwing caused by lack of match between tool with learners. Lack of variation in learning especially substitute lat alternatives. Therefore the purpose of this study, improving learning outcomes through a tail ball game modification approach. The method used with the form of classroom action research, with the subject of research is the students of class IV State Elementary School 22 Sungai Kakap Â Kabupaten Kubu Raya, amounting to 35 people. The results of research conducted by the study provide a positive impact on students because it consists of cycle I and cycle II in the form of planning, implementation, observation and reflection. Learning cycle I students who have just graduated amounted to 29 students or 82,% while students who have not graduated amounted to 6 students or 18% then proceeded to cycle II so that students have the opportunity to repair the turbo throw then it is necessary to learn with the ball tail then just said to pass 100 % or 35 students who did not pass 0%. Keyword: Throw Turbo, Tailed Ball